Answer:
4 grams............
Step-by-step explanation:
Answer:
C. (5x^3-7)(2x^2+1)
Step-by-step explanation:
Given expression is,
10x^5+5x^3-14x^2-7
=10x^5-14x^2 + 5x^3 - 7 (By the commutative property)
=2x^2(5x^3-7)+5x^3-7 (Taking 2x^3 common from first two terms )
=(5x^3-7)(2x^2+1) (Taking 5x^3-7 common from both terms)
\implies 10x^5+5x^3-14x^2-7=(5x^3-7)(2x^2+1)
Hence, Option C is correct
Answer:
wheres the question
Step-by-step explanation:
Answer:
Step-by-step explanation:
i know u do rise over run so that will give you uor answer
im not very smart when it comes to math
sorry i couldnt help